2005
DOI: 10.1038/sj.bjc.6602861
|View full text |Cite
|
Sign up to set email alerts
|

Ectodomain shedding of the hypoxia-induced carbonic anhydrase IX is a metalloprotease-dependent process regulated by TACE/ADAM17

Abstract: Carbonic anhydrase IX (CA IX) is a transmembrane protein whose expression is strongly induced by hypoxia in a broad spectrum of human tumours. It is a highly active enzyme functionally involved in both pH control and cell adhesion. Its presence in tumours usually indicates poor prognosis. Ectodomain of CA IX is detectable in the culture medium and body fluids of cancer patients, but the mechanism of its shedding has not been thoroughly investigated. Here, we analysed several cell lines with natural and ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 28 publications
5
100
1
1
Order By: Relevance
“…Although our observations were inconsistent with the proposal that hypoxia and HIF-1 are the sole regulators of CAIX expression and thus shedding (Zatovicova et al, 2005), one cannot exclude that shedding occurs at hypoxic metastatic sites. Although the precise molecular mechanism of regulated CAIX shedding remains to be clarified, previous studies showed that dysregulation of HIF-1a could be caused by mutation in the von Hippel-Lindau (VHL) tumour suppressor gene or activation of the epidermal growth factor receptor (EGFR) (Semenza, 2003).…”
Section: Discussioncontrasting
confidence: 57%
“…Although our observations were inconsistent with the proposal that hypoxia and HIF-1 are the sole regulators of CAIX expression and thus shedding (Zatovicova et al, 2005), one cannot exclude that shedding occurs at hypoxic metastatic sites. Although the precise molecular mechanism of regulated CAIX shedding remains to be clarified, previous studies showed that dysregulation of HIF-1a could be caused by mutation in the von Hippel-Lindau (VHL) tumour suppressor gene or activation of the epidermal growth factor receptor (EGFR) (Semenza, 2003).…”
Section: Discussioncontrasting
confidence: 57%
“…CA9 expression in tumor and stromal tissue can be considered as a marker of hypoxia (14). Ectodomain shedding of CA9 mainly occurs by hypoxic cancer cells and leads to an increase in circulating levels (39). Therefore, the use of circulating CA9 may provide a noninvasive means of assessing tumor hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…At least 13 human CA isoenzymes that exhibit catalytic activity are distributed in various human organs, tissues and subcellular compartments, playing an important role in essential cellular processes such as pHe and pHi regulation, secretion of electrolytes, respiration and biosynthetic reactions that require CO 2 and HCO 3 -as substrates (e.g. lipogenesis, gluconeogenesis and ureagenesis) (Thiry et al, 2006;Zatovicova et al, 2005). CA9, the only transmembrane CA isoenzyme with an extracellular active site and an NH 2 -terminal proteoglycan-like region, is also implicated in cell adhesion as well as in acid-base balancing and intercellular communication (Robertson et al, 2004;Svastova et al, 2003).…”
Section: Introductionmentioning
confidence: 99%